Geographical dimensions of the high ground water levels in the city of Hit - Assist prof Dr. Mishaal Faisal Gdhab (الأستاذ, 2018)
We tried in this research can offer a simple explanation for the problem of high groundwater levels in the city of Hit. And its repercussions on economic, environmental, social and health aspects in the city,We were checked in the causes and dimensions and give a scientific vision in order to overcome the obstacles.We have adopted the style inductive and field survey and analysis of the questionnaire, which was distributed to a sample of homes form.The study found that the most important results of the natural world (geology and surface) that a significant impact on this phenomenon. Also it left a large, social and environmental health and economic impacts on the city and its inhabitants. We greet you see the ground and salted Rookery, ponds, swamps and pollutants .... and housing that lacks the gardens. And walls cracked by moisture and become the most residential and public buildings infected with diseases buildings and extinction and the many diseases that affect the health of urban populations and the dispersion of land use and contamination of optical and environmental hit even sources of water supply and of the Euphrates River city and provided a scientific vision for treatment, among them the work of bumpers impede the progress of the underground water and increasing the discharge Trocars the old lining